Improvement of L-Tryptophan Production in Escherichia coli Using Biosensor-Based, High-Throughput Screening and Metabolic Engineering - Zhenghao Gao; Fengli Wu; Zhidan Zhang; Xu Zhang; Yuansen Hu; Qinhong Wang; Shuaibing Zhang (Fermentation)
The demand for L-tryptophan (L-Trp) has been rapidly increasing across various industries, including pharmaceuticals, food, and animal feed. However, traditional production methods have been unable to efficiently meet this growing demand. Hence, this study aimed to develop strategies for enhancing L-Trp production in Escherichia coli. Firstly, an L-Trp-producing strain was selected and subjected to atmospheric and room temperature plasma (ARTP) mutagenesis to generate a mutant library. This was followed by high-throughput screening using an L-Trp-specific riboswitch and a yellow fluorescent protein (YFP)-based biosensor in a flow cytometric cell sorting (FACS) system. Among the screened mutants, GT3938 exhibited a 1.94-fold increase in L-Trp production. Subsequently, rational metabolic engineering was applied to GT3938 by knocking out the L-Trp intracellular transporter gene (tnaB), enhancing the expression of the aromatic amino acid exporter (YddG) and optimizing precursor supply pathways. The resulting strain, zh08, achieved an L-Trp titer of 3.05 g/L in shake-flask fermentation, representing a 7.71-fold improvement over the original strain. This study demonstrated an effective strategy for industrial strain development by integrating biosensor-assisted, high-throughput screening with rational metabolic engineering.